Exploring Teachers' Professional Development on Socioscientific Issues and Model-Based Learning: A Multiple Case Study - Durak, Benzegul; Topcu, Mustafa Sami (SPRINGER, 2025)
This study proposes a three-phase professional development (PD) program for middle school science teachers and aims to investigate their engagement with the Socioscientific Issue and Model-Based Learning (SIMBL) framework. It follows a multiple-case study design, and the main data sources of the study are semi-structured interviews, while the secondary data sources include developed SIMBL units, field notes of the PD program, classroom observations of the lessons, and unstructured phone calls/messages. The semi-structured interviews comprise pre- and post-PD program interviews as well as post-implementation interviews. Employing the Interconnected Model of Professional Growth framework for data analysis, teachers are categorized into three distinct groups: proactive, collaborative, and teacher-led. Findings highlight how teacher beliefs and prior experiences shape their ability to integrate SIMBL into classroom practices. The study emphasizes the critical role of sustained PD, reflective practices, and alignment with teacher beliefs in facilitating the effective implementation of innovative teaching frameworks. Ultimately, the SIMBL framework was found to enhance student engagement with socioscientific issues by fostering critical thinking, systems-based reasoning, and media literacy, contributing to science education.
Keywords: SOCIO-SCIENTIFIC ISSUES; SCIENCE-EDUCATION; KNOWLEDGE; EXPLANATIONS; PERCEPTIONS; STUDENTS; Education & Educational Research; History & Philosophy of Science